2005
DOI: 10.1007/bf02978209
|View full text |Cite
|
Sign up to set email alerts
|

MAP Kinase activation is required for the MMP-9 induction by TNF-stimulation

Abstract: MMP-9 is a metalloproteinase capable of basement membrane degradation in vivo. Expression of MMP-9 can be found in normal conditions such as trophoblasts, osteoclasts, and leukocytes and their precursors. They also occur as well as in pathological conditions, such as the invasive growth of primary tumors, metastasis, angiogenesis, rheumatoid arthritis, and periodontal diseases. MMP-9 upregulation can be highly induced by a wide range of agents. These agents include growth factors, cytokines, cell-cell, and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…ERK1/2, JNK, and p38 MAPK) in the production of MMP-9 in response to TNF-␣ appears to be cell-specific. For example, ERK1/2 but not JNK or p38 MAPK was found to be involved in TNF-␣-induced MMP-9 expression in a human monocyte cell line (53). In human trophoblastic cells, TNF-␣-induced MMP-9 expression, secretion, and activity were completely blocked by JNK and ERK1/2 inhibitors but not by p38 MAPK inhibitors (54).…”
Section: Discussionmentioning
confidence: 94%
“…ERK1/2, JNK, and p38 MAPK) in the production of MMP-9 in response to TNF-␣ appears to be cell-specific. For example, ERK1/2 but not JNK or p38 MAPK was found to be involved in TNF-␣-induced MMP-9 expression in a human monocyte cell line (53). In human trophoblastic cells, TNF-␣-induced MMP-9 expression, secretion, and activity were completely blocked by JNK and ERK1/2 inhibitors but not by p38 MAPK inhibitors (54).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have indicated that MAPK pathways are involved in the expression of MMP-9 (33,34). To explore whether the inhibitory effect of aspirin on the expression of MMP-9 was mediated through the MAPK pathway, the phosphorylated protein levels of ERK1/2, JNK and p38 were examined by western blot in RAW264.7 cells pre-treated with aspirin and then with TNF-α for various times (0, 10, 20, 30 and 60 min).…”
Section: Effect Of Aspirin On the Inhibition Of Erk1/2 Jnk And P38mentioning
confidence: 99%
“…Many of these signals are generated during the LPS response or during infection. For instance, interleukin-1␤ (IL-1␤) and TNF, both of which are important cytokines in endotoxemia and sepsis, can induce MMP genes (60,129). In turn, MMPs can activate these cytokines and/or release them by shedding, generating a positive feedback loop.…”
Section: Different Cell Types Can Produce Mmps In Response To Lps Sumentioning
confidence: 99%